Cardiac Dysfunction in the Sigma 1 Receptor Knockout Mouse Associated With Impaired Mitochondrial Dynamics and Bioenergetics. Issue 20 (16th October 2018) - Abdullah, Chowdhury S.; Alam, Shafiul; Aishwarya, Richa; Miriyala, Sumitra; Panchatcharam, Manikandan; Bhuiyan, Mohammad Alfrad Nobel; Peretik, Jonette M.; Orr, A. Wayne; James, Jeanne; Osinska, Hanna; Robbins, Jeffrey; Lorenz, John N.; et al.
Abstract : Background: The Sigma 1 receptor (Sigmar1) functions as an interorganelle signaling molecule and elicits cytoprotective functions. The presence of Sigmar1 in the heart was first reported on the basis of a ligand‐binding assay, and all studies to date have been limited to pharmacological approaches using less‐selective ligands for Sigmar1. However, the physiological function of cardiac Sigmar1 remains unknown. We investigated the physiological function of Sigmar1 in regulating cardiac hemodynamics using the Sigmar1 knockout mouse (Sigmar1 −/− ). Methods and Results: Sigmar1 −/− hearts at 3 to 4 months of age showed significantly increased contractility as assessed by left ventricular catheterization with stimulation by increasing doses of a β1 ‐adrenoceptor agonist. Noninvasive echocardiographic measurements were also used to measure cardiac function over time, and the data showed the development of cardiac contractile dysfunction in Sigmar1 −/− hearts as the animals aged. Histochemistry demonstrated significant cardiac fibrosis, collagen deposition, and increased periostin in the Sigmar1 −/− hearts compared with wild‐type hearts. Ultrastructural analysis of Sigmar1 −/− cardiomyocytes revealed an irregularly shaped, highly fused mitochondrial network with abnormal cristae. Mitochondrial size was larger in Sigmar1 −/− hearts, resulting in decreased numbers of mitochondria per microscopic field. In addition, Sigmar1 −/− hearts showed altered expression of mitochondrial dynamics regulatory proteins. Real‐time oxygen consumption rates in isolated mitochondria showed reduced respiratory function in Sigmar1 −/− hearts compared with wild‐type hearts. Conclusions: We demonstrate a potential function of Sigmar1 in regulating normal mitochondrial organization and size in the heart. Sigmar1 loss of function led to mitochondrial dysfunction, abnormal mitochondrial architecture, and adverse cardiac remodeling, culminating in cardiac contractile dysfunction.